Resonant Young’s Slit Interferometer for Sensitive Detection of Low-Molecular-Weight Biomarkers - Stefanus Renaldi Wijaya; Augusto Martins; Katie Morris; Steven D. Quinn; Thomas F. Krauss (Biosensors)
The detection of low-molecular-weight biomarkers is essential for diagnosing and managing various diseases, including neurodegenerative conditions such as Alzheimer’s disease. A biomarker’s low molecular weight is a challenge for label-free optical modalities, as the phase change they detect is directly proportional to the mass bound on the sensor’s surface. To address this challenge, we used a resonant Young’s slit interferometer geometry and implemented several innovations, such as phase noise matching and optimisation of the fringe spacing, to maximise the signal-to-noise ratio. As a result, we achieved a limit of detection of 2.9 × 10−6 refractive index units (RIU). We validated our sensor’s low molecular weight capability by demonstrating the detection of Aβ-42, a 4.5 kDa peptide indicative of Alzheimer’s disease, and reached the clinically relevant pg/mL regime. This system builds on the guided mode resonance modality we previously showed to be compatible with handheld operation using low-cost components. We expect this development will have far-reaching applications beyond Aβ-42 and become a workhorse tool for the label-free detection of low-molecular-weight biomarkers across a range of disease types.